A portal of educational resources: providing evidence for matching pedagogy with technology - Nicoletta Blas; Alessandro Fiore; Luca Mainetti; Roberto Vergallo; Paolo Paolini (Association for Learning Technology, 2014)
The TPACK (Technology, Pedagogy and Content Knowledge) model presents the three types of knowledge that are necessary to implement a successful technology-based educational activity. It highlights how the intersections between TPK (Technological Pedagogical Knowledge), PCK (Pedagogical Content Knowledge) and TCK (Technological Content Knowledge) are not a sheer sum up of their components but new types of knowledge. This paper focuses on TPK, the intersection between technology knowledge and pedagogy knowledge - a crucial field of investigation. Actually, technology in education is not just an add-on but is literally reshaping teaching/learning paradigms. Technology modifies pedagogy and pedagogy dictates requirements to technology. In order to pursue this research, an empirical approach was taken, building a repository (back-end) and a portal (front-end) of about 300 real-life educational experiences run at school. Educational portals are not new, but they generally emphasise content. Instead, in our portal, technology and pedagogy take centre stage. Experiences are classified according to more than 30 categories ('facets') and more than 200 facet values, all revolving around the pedagogical implementation and the technology used. The portal (an innovative piece of technology) supports sophisticated 'exploratory' sessions of use, targeted at researchers (investigating the TPK intersection), teachers (looking for inspiration in their daily jobs) and decision makers (making decisions about the introduction of technology into schools).